Infraspecific variations in essential oil and glandular trichomes in Nepeta heliotropifolia - MAHBOBEH YARMOOHAMMADI; SEYED MEHDI TALEBI; MAJID GHORBANI NOHOOJI (Society for Indonesian Biodiversity, 2017)
Yarmoohammadi M, Talebi SM, Nohooji MG. 2017. Infraspecific variations in essential oil and glandular trichomes in Nepeta heliotropifolia. Biodiversitas 18: 964-970. Nepeta heliotropifolia Lam. (Labiatae) is one of the perennial medicinal and aromatic plants, naturally grows in different regions of Iran. The essential oil composition of aerial parts and also the micromorphology and distribution of foliar trichomes of N. heliotropifolia from two different regions of Iran were studied. The extracted essential oils were significantly composed of caryophyllene oxide and phytol, which were quantified by GC and identified based on their GC/MS spectra. The essential oil compositions differed greatly with habitat as well as former investigations. Phytol was quantified between 0.75-10. 29% of the total essential oil, but caryophyllene oxide was quantified between 3.90-12.17% of the total essential oil. Trichomes investigations showed that leaves bear an indumentum of glandular and non-glandular hairs. Two main kinds of glandular trichomes were observed; peltate and capitate. The numbers of capitate and peltate trichomes varied between populations. Such great differences in the essential oil composition may be attributed to chemotype creation and also an adaptation of these populations to particular habitats.